Pure cellulose paper ageing in sealed vessels. Autocatalytic depolymerization model revisited - Zervos, Spiros; Choulis, Konstantinos; Panagiaris, Georgios (Journal of Integrated Information Management, 2019)
Purpose - In the framework of the EU funded INVENVORG project (Thales Research Funding Program – NRSF), the natural and artificial ageing of bone, wood, textiles, parchment and paper were investigated. Design/methodology/approach - In this work, the results of accelerated ageing on pure cellulose paper in sealed vessels are reported. The properties studied include the degree of polymerization (which was converted to the percentage of broken glyosidic bonds), the tearing resistance, the pH and the L* and b* coordinates of the CIEL*a*b* color system. Ageing was performed in sealed vessels at 90°C και 76% RH for periods of 20, 40, 60, 80, 100, 120 and 140 days. Findings - The results indicated an overall deterioration of all paper properties, which accelerates with time because of the production of volatile acidic species (autocatalysis). The evolution of paper properties through time was modeled efficiently by use of the equations proposed by Zervos and Moropoulou (2005) for the autocatalytic acid hydrolysis of pure cellulose paper, which were shown that also apply for following the changes of tearing resistance. The applicability of the model equations was also verified for other paper properties, such as the percentage of broken bonds (δ%) and the L* and b* coordinates of the CIEL*a*b* color system.